Extended Release of Ciprofloxacin from Commercial Silicone-Hydrogel and Conventional-Hydrogel Contact Lenses containing Vitamin E Diffusion Barriers - Al Atrach, Mehdi (University of Waterloo, 2024)
Abstract Purpose: Contact Lenses (CLs) are ophthalmic devices globally used by more than 140 million people to correct vision problems. To overcome the drawbacks of eye drops, drug-delivering CLs have been given much attention because they increase the bioavailability of ocular drugs, resulting in increasing efficacy and reducing potential side effects. These systems typically have a burst and rapid release. To address these concerns, this study aims to develop a contact lens-based ocular drug delivery system using vitamin E as a diffusion barrier to extend the release duration of ciprofloxacin. Methods: The purpose of the first experiment in the thesis (Chapter 3) was to develop and evaluate drug delivery contact lenses: Four commercial silicone hydrogel lenses (senofilcon A, lotrafilcon B, comfilcon A, and samfilcon A) and one conventional hydrogel lens (etafilcon A) were soaked for 24 hours in various concentrations of vitamin E dissolved in ethanol (0.0125 - 0.2 g/mL). The amount of vitamin E loaded was calculated by measuring the dry lens weight before and after vitamin E loading. The lenses were loaded with ciprofloxacin for 24 hours. The amount of ciprofloxacin loaded was determined using an extraction protocol. The drug release was evaluated in phosphate-buffered saline solution in an amber glass vial, at 37°C with shaking. The amount of ciprofloxacin released was measured using a UV-VIS spectrophotometer at 270 nm. The second experimental chapter (Chapter 4) aimed to evaluate the effect of ciprofloxacin loading duration on the uptake and release profiles of senofilcon A. This was done by applying the same method described in Chapter 3, except ciprofloxacin loading durations for senofilcon A were 24 hours and 7 days. Results: The data showed that there was a decrease in ciprofloxacin loading with increasing amounts of vitamin E loaded into the silicone hydrogel lenses. For each lens type, there was an optimal amount of vitamin E loaded that extended the release duration of the drug from 1 hour (without vitamin E) to as long as 16 hours. Senofilcon A with 0.025 g/mL vitamin E loaded exhibited the longest-sustained release for all lens types, achieving 16 hours of release. In contrast, vitamin E loaded into etafilcon A had no effect on the amount of drug loaded or the release duration. The data obtained in Chapter 4 showed no significant difference in the uptake and release profiles among the different loading durations (24 hours and 7 days), except in lenses with 0.025 and 0.05 g/mL vitamin E concentrations, which absorbed and released more drugs in the 7-day loading duration experiment. In addition, senofilcon A longest release duration (16 hours) achieved in chapter 3 did not further increase in chapter 4 after increasing the drug loading duration to 7 days. Conclusion: Vitamin E can be used as a diffusion barrier with commercial silicone hydrogel lenses to provide sustained release of ciprofloxacin. The results suggest that vitamin E may form blockages in channels within a silicone hydrogel lens material, thereby forcing a longer path for drugs to diffuse into and out of the lens material. There is an optimal amount of vitamin E that needs to be loaded to extend the release duration, and this is lens material dependent. Additionally, increasing the drug loading duration to 7 days was not enough to increase the drug-loaded amount, and subsequently the release duration specifically for senofilcon A loaded with 0.2 g/ml vitamin E concentration.
Keywords: Vitamin E; Ciprofloxacin; ophthalmic drug delivery; Contact lenses; extended release